1987
DOI: 10.1148/radiology.163.3.2437611
|View full text |Cite
|
Sign up to set email alerts
|

Benign prostatic hypertrophy: retrograde transurethral dilation of the prostatic urethra in humans. Work in progress.

Abstract: Retrograde transurethral balloon dilation of the prostatic urethra was performed in five human volunteers with benign prostatic hypertrophy. Each patient underwent cystoscopy, uroflow studies, voiding cystourethrography, retrograde urethrography, and magnetic resonance imaging before dilation and at defined intervals afterward. The longest follow-up to date is 8 months. Patients were given topical anesthetics and mild sedatives, and dilation was performed with a 25-mm urethroplasty balloon catheter inflated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…Several reports have revealed that concentric dilatation using torpedo-type balloons can be employed for postinflammatory and posttraumatic urethral strictures, and is more precise and less traumatic to the urethra [1,2], However, bal loon dilatation for the entire urethral stricture has been scarcely reported. Recently, balloon dilatation of the prostatic urethra with a large balloon catheter has been applied safely and successfully for benign prostatic hy perplasia [3], We have performed balloon dilatation of the prostatic urethra for patients with urinary retention due to benign prostatic hyperplasia with satisfactory results [4]. Then, we treated 2 cases of entire urethral stricture using a balloon dilatation catheter and also obtained a satisfactory outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have revealed that concentric dilatation using torpedo-type balloons can be employed for postinflammatory and posttraumatic urethral strictures, and is more precise and less traumatic to the urethra [1,2], However, bal loon dilatation for the entire urethral stricture has been scarcely reported. Recently, balloon dilatation of the prostatic urethra with a large balloon catheter has been applied safely and successfully for benign prostatic hy perplasia [3], We have performed balloon dilatation of the prostatic urethra for patients with urinary retention due to benign prostatic hyperplasia with satisfactory results [4]. Then, we treated 2 cases of entire urethral stricture using a balloon dilatation catheter and also obtained a satisfactory outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The technique of balloon urethroplasty in normal animals and humans with prostatic hypertrophy has been described in detail [4][5][6] In our patient in whom cystoscopy was repeated 1 month after the procedure, persistent separation of the pmostatic lobes was found.…”
Section: Materials Subjects and Methodsmentioning
confidence: 97%
“…Once the spiral catheter was positioned correctly, the 17-Fr urethroscope was used to inspect the distal end of the spiral. An X-ray was taken for recording the position of the Patients with benign prostatic hyperplasia and uri nary retention usually need prostatic resection to void [1], If the operative riks is too high, other therapeutic modalities have been advocated, such as intraprostatic balloon dilatation [2], luteinizing hormone-releasing hormone agonist [3], cryosurgery [4], prostatic hyper thermia [5] and transurethral incision of the prostate under local anesthesia [6]. The intraprostatic spiral is another alternative to relieve obstruction of the bladder outlet.…”
Section: Introductionmentioning
confidence: 99%